2020
DOI: 10.1007/s00784-020-03281-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a screening model for diabetes mellitus in patients with periodontitis in dental settings

Abstract: Objectives To identify predictors in patient profiles and to develop, internally validate, and calibrate a screening model for diabetes mellitus (DM) in patients with periodontitis in dental settings Materials and methods The study included 204 adult patients with periodontitis. Patients’ socio-demographic characteristics, general health status, and periodontal status were recorded as potential predictors. The diabetic status was considered the outcome, classified into no DM, prediabetes (pre-DM), or DM. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Some studies also collected self‐reported measures (Herman et al, 2015), radiographic bone loss (Holm et al, 2016; Heji et al, 2020) and salivary biomarkers (Grigoriadis et al, 2021). Six studies used clinical periodontitis case definitions; namely the CDC/AAP (Holm et al, 2016; Su et al, 2020), the 2017 World Workshop (Grigoriadis et al, 2021) and ad hoc definitions (Herman et al, 2015; Hegde et al, 2019; Montero et al, 2021). All studies used multiple regression for model development, except for one study which used machine learning (Hegde et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies also collected self‐reported measures (Herman et al, 2015), radiographic bone loss (Holm et al, 2016; Heji et al, 2020) and salivary biomarkers (Grigoriadis et al, 2021). Six studies used clinical periodontitis case definitions; namely the CDC/AAP (Holm et al, 2016; Su et al, 2020), the 2017 World Workshop (Grigoriadis et al, 2021) and ad hoc definitions (Herman et al, 2015; Hegde et al, 2019; Montero et al, 2021). All studies used multiple regression for model development, except for one study which used machine learning (Hegde et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…All studies but one (Lalla et al, 2011) had less than 10 events per variable. In addition, four studies did not include all participants in the analysis (Herman et al, 2015; Hegde et al, 2019; Heji et al, 2020; Su et al, 2020), three dichotomized periodontal predictors using arbitrary thresholds (Herman et al, 2015; Holm et al, 2016; Montero et al, 2021), three used an inappropriate method to select predictors for inclusion in the model (Holm et al, 2016; Grigoriadis et al, 2021; Montero et al, 2021) and one did not account for the complexities in the data, namely sampling fractions in a case–control study (Hegde et al, 2019). Finally, the two studies that reported a PPM (Lalla et al, 2011; Montero et al, 2021) did not assess model performance in terms of both discrimination and calibration, did not account for model overfitting and optimism and did not report the weights assigned to predictors for clinical use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PreDM was found in 9.9% of unaware dental patients in Sweden (242), 28.7% in the US (235), and 46.6% among patients with Dutch periodontal (243). Such screening in dental offices is well-accepted by patients (245)(246)(247), dentists (246)(247)(248)(249)(250) and physicians (251), and their professional organizations (252), and can lead to positive lifestyle changes and decreased HbA1c level (253,254).…”
Section: Screening For T2dm In the Dental Officementioning
confidence: 99%